Compostagem de resíduos agroindustriais: revolvimento, inoculação e condições ambientais - Carneiro, Leocir José (2012)
This trial aimed at testing the turning, cover courtyard and inoculation with a Commercial Biological Product (CBP) at the composite period and the produced compost quality using agro-industrial residues. The experiment was carried out at the Experimental Center of Agricultural Engineering (NEEA), at Western Paraná State University (UNIOESTE). The following wastes were used during the composting process from the activities developed by the Agricultural Cooperative Consolata - COPACOL: hatchery waste, flotation sludge, ash and remaining coal from boiler, solid fraction of swine manure, solid fraction of waste from trucks washing and waste from cleaning and pre-cleaning of cereals. Twelve treatments were performed and composed of three combinations of shift plowing frequencies with these conditions: uncovered and covered courtyard without and with CBP inoculation. The windrows were piled with 300 kg of weight each, so that each one could have the same composition. The pile temperature was daily monitored. The parameters as reduced mass, volume, total and volatile solids were weekly monitored. Electrical conductivity, pH, carbon and nitrogen were measured at the beginning, 28, 56 days and at the end of the process. The contents of P, K, Mg, Ca, Na, Zn, Cu, Mn and Fe were determined at the beginning and end of the composite process. The electrical conductivity, pH, carbon and nitrogen were measured at the beginning, at 28, 56 days and at the end of the process. The levels of P, K, Mg, Ca, Na, Zn, Cu, Mn and Fe were determined at the beginning and end of the composite process. The coverage at composite courtyard showed significant effect on volume and nitrogen decreases (p<0.05) and increases electrical conductivity, contents of Na, Mg, K and composite time (p <0.05). The use of frequent turnings at the beginning of the process allowed greater volume reduction and composting reduced the time within 20 days (p <0.05). However, there were greater losses of N, C, and consequently the C / N ratio. The frequency of shift plowing was twice a week on the first month (F2), so it was more effective in keeping nitrogen in the pile. The CBP use was not significant for any of the variables (p> 0.05) and pH, concentration of P, Ca, and micronutrients were not affected by any of the variables.